Surgical Treatment of Anorectal Crohn Disease - Lewis, Robert T.; Bleier, Joshua I. S. (Clinics in Colon and Rectal Surgery, 2013)
Crohn disease involves the perineum and rectum in approximately one-third of patients. Symptoms can range from mild, including skin tags and hemorrhoids, to unremitting and severe, requiring a proctectomy in a small, but significant, portion. Fistula-in-ano and perineal sepsis are the most frequent manifestation seen on presentation. Careful diagnosis, including magnetic resonance imaging or endorectal ultrasound with examination under anesthesia and aggressive medical management, usually with a tumor necrosis factor-alpha, is critical to success. Several options for definitive surgical repair are discussed, including fistulotomy, fibrin glue, anal fistula plug, endorectal advancement flap, and ligation of intersphincteric fistula tract procedure. All suffer from decreased efficacy in patients with Crohn disease. In the presence of active proctitis or perineal disease, no surgical therapy other than drainage of abscesses and loose seton placement is recommended, as iatrogenic injury and poor wound healing are common in that scenario.
Keywords: anorectal; Crohn disease; fistula; abscess; flap; plug; ligation of intersphincteric fistula tract (LIFT); immunomodulators; fistulotomy